FAKTOR YANG BERPENGARUH TERHADAP PREFERENSI PENGHUNI MEMILIH PERUMAHAN DI KECAMATAN TAMPAN, KOTA PEKANBARU - Gina Purnama Sari; Zulfan Saam; Ferry Fatnanta (Jurnal Ilmu Lingkungan, 2016)
Housing construction in Tampan subdistrict developed rapidly, either on a small scale, medium or large where developers offer a range of housing alternative to attract customers. The choice of housing is more varied, so that the resident have essential factors as a consideration in selecting a residential location. This study aimed to analise the factors that influence resident preferences in selecting housing in Tampan sub district. Colecting data is using surveys method and interviews with conducted sample selection through stratified random sampling of 100 respondents was obtained. The results showed that from the Chi Square test obtained eleven indicators relating to resident preferences are residents income, the physical condition of the area, the location of the area, environmental comfort, developers offers, the basic physical needs of a healthy home, road access, availability of electricity, sewerage systems, social institutional and accessibility. However, the results obtained by logistic regression analysis of factors that most affect the resident preferences in selecting housing in Tampan sub district is the location of the area, road access , sewerage systems and accessibility.